Carcinoid tumor of the ileum. Carcinoid syndrome - Cassinelli, Daniel; Estefan, Alberto (Cirugía del Uruguay, 2021)
The paper discusses one case of carcinoid tumor of the terminal ileon with multiple metastasis in the liver and ascitis, accompanied by a carcinoid syndrome. While the patient is in hospital he presents symptoms of obstruction in the small intestine and is operated. There is a tumor and metastasis. In tracing tumor histology the rich associated symptomatology is interpreted in the diagnosis